SOCIALIZATION OF PROCEDURES FOR THE IMPLEMENTATION OF CLEFT LIP AND CLEFT SKY SOCIAL SERVICE AT JIMMY MEDIKA BORNEO MOTHER AND CHILD HOSPITAL (Jurnal Abdimas Administrasi Kesehatan, 2021)
Prosedurs Cleft Lip and Cleft Sky is a condition in which there is an abnormal cleft in the upper lip and roof of the mouth that occurs when several parts fail to merge together during early pregnancy. The lip and palate develop separately, making it possible for the baby to be born with only the lip of the clapse, only the cleft palate sky or a combination of both. This community service activity is a facility and infrastructure that provides socialization of procedures for the implementation of cleft lip and cleft sky social services at the Jimmy Medika Borneo Mother and Child Hospital, Samarinda, East Kalimantan on June 15-16, 2021. Socialization of procedures for the implementation of cleft lip and cleft sky social service at Jimmy Medika Borneo Mother and Child Hospital well categorized and running smoothly.